Standardization of Culture Medium for Somatic Embryogenesis of Rice Var. MTU 7029 - Mondal, Sananda; Singh, R. P.; Bose, Bandana (International Journal of Bio-resource and Stress Management, 2023)
The aim of the study is to establish a routine procedure for high frequency plant regeneration from in vitro raised embryogenic callus of indica rice var. MTU 7029. In the present piece of work, various concentrations of surfactants [sodium hypochlorite (10 to 30%) and mercuric chloride (0.01 to 1%)] were tested and best concentration of surfactants was chosen according to the parameters like callus induction percentage and its growth as well as status of contamination. On the basis of available data of the said parameters, 0.1% mercuric chloride has shown best performance in all the aspect for surface sterilization of mature rice seeds for 5 minutes and the percentage of the contamination was also very less. The effect of synthetic auxin [2,4-D (0 to 4 mg L-1)], cytokinin [kinetin (0 to 1 mg L-1)], sucrose (0 to 50 g L-1), agar (6-16 g L-1) and growth medium (MS, N6 and LS) on callus induction were optimized to achieve high frequency plant regeneration from fresh embryogenic callus without further subculture. Results suggests that 2 mg L-1 2, 4-D, 30 g L-1 sucrose, 8 g L-1 agar and MS basal medium were best for embryogenic callus induction. From the present piece of work an efficient protocol was developed for in vitro embryogenic callus formation.